Correlation of Clinical and Computed Tomographic Diagnosis in Patients of Cerebrovascular Disease - Sarker, RN; Rabbi, AF; Hossain, MZ; Hossain, A; Quddus, MA; Mohammad, QD; Chowdhury, N; Ramiz, S (Journal of Dhaka Medical College, 2011)
Objective: To find out the correlation of clinical and computed tomographic diagnosis in patients of cerebrovascular disease (CVD). Materials and Methods: Clinical and computed tomographic diagnoses were compared in 133 patients who were diagnosed clinically as CVD and underwent computed tomography (CT) scan of brain for confirmation of their clinical condition. The study was done in Dhaka Medical College Hospital, Dhaka from July, 2003 to June, 2004. Results: Of the 99 clinically diagnosed infarct cases, 82 cases were proved to be correct on CT scan. 25 out of the 34 provisionally diagnosed cases of haemorrhagic CVD were confirmed to have the same by CT scan. 4 cases were found normal and 10 cases as intracranial tumours in CT scan which were clinically diagnosed as CVD. 6 cases diagnosed clinically as haemorrhagic CVD were finally proved to be ischaemic CVD by CT scan and 6 cases diagnosed clinically as ischaemic infarction were confirmed as intracranial haemorrhage. No significant difference was found in between clinical diagnosis and CT scan diagnosis (p> 0.001). Conclusion: Clinical and CT scan diagnosis in patients of cerebrovascular disease correlate well. Therefore, a careful neurologic assessment combined with CT scan of brain is useful in diagnosing specific cerebrovascular lesion for specific therapeutic implications with high certainty. Moreover, CT scan can exclude other intracranial lesions those mimic CVD clinically. Key words: Cerebrovascular disease (CVD); clinical diagnosis; computed tomography (CT). DOI: 10.3329/jdmc.v19i2.7078 J Dhaka Med Coll. 2010; 19(2) : 102-108